Efektivitas Biofilter dengan Media Papan Pakis dan Sistem Aerasi Intermittent dalam Mengurangi COD dan NH3-N pada Limbah Cair Rumah Potong Ayam - Flaherti Maharani; Raden Kokoh Haryo Putro; Praditya Sigit Ardisty Sitogasa (Jurnal Serambi Engineering, 2025)
Wastewater generated from poultry slaughterhouses generally contains high levels of organic matter and ammonia, which can contaminate aquatic environments if not properly treated. The high organic content contributes to elevated COD levels, while ammonia can be toxic to aquatic organisms. This study was conducted to evaluate the performance of a biofilter system with intermittent aeration (anoxic–oxic combination) using tree fern board and bioring media in reducing COD and NH₃-N concentrations. The tested aeration durations included 3 hours (1 hour anoxic, 2 hours oxic), 6 hours (2 hours anoxic, 4 hours oxic), 9 hours (3 hours anoxic, 6 hours oxic), and 12 hours (4 hours anoxic, 8 hours oxic). The experimental results showed that the bioring medium exhibited better performance than the tree fern board, with the optimum condition achieved at a 12-hour hydraulic retention time, resulting in COD and NH₃-N reductions of 93.41% and 88.21%, respectively. Overall, the findings indicate that a bioring-based biofilter with intermittent aeration has strong potential as an effective and environmentally friendly alternative technology for treating poultry slaughterhouse wastewater.